2004
DOI: 10.1158/1078-0432.ccr-0200-03
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity at the Thymidylate Synthase ( TS ) Locus on Chromosome 18 Affects Tumor Response and Survival in Individuals Heterozygous for a 28-bp Polymorphism in the TS Gene

Abstract: Thymidylate synthase (TS), the target enzyme of the fluoropyrimidine class of drugs, has a 28-bp repeat polymorphism in the promoter region that has been associated with response of tumors to 5-fluorouracil-based therapy. Patients homozygous for the double repeat (2R/2R) in the TS gene have an overall better outcome from treatment than patients homozygous for the triple repeat (3R/3R). However, due to loss of heterozygosity at the TS locus on chromosome 18 in cancer cells, heterozygous 2R/3R individuals can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 27 publications
7
84
0
7
Order By: Relevance
“…On the other hand, a recent study indicated that determination of genetic polymorphisms in peripheral blood may not be representative for the situation in tumour tissue. Thus, Uchida et al (2004) have shown that individuals heterozygous for the 28-bp polymorphism in the TS gene may have cancers that are homozygous for this polymorphism due to loss of one allele during carcinogenesis. Furthermore, they could show that the response to 5-FU-based chemotherapy in these cases was comparable to cases where the entire individual was homozygous.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study indicated that determination of genetic polymorphisms in peripheral blood may not be representative for the situation in tumour tissue. Thus, Uchida et al (2004) have shown that individuals heterozygous for the 28-bp polymorphism in the TS gene may have cancers that are homozygous for this polymorphism due to loss of one allele during carcinogenesis. Furthermore, they could show that the response to 5-FU-based chemotherapy in these cases was comparable to cases where the entire individual was homozygous.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of 30 stage IV colorectal cancer patients, LOH was observed in 17 out of 22 heterozygotes. 38 The presence of a TSER*3 allele (homozygous TSER*3, heterozygous and TSER*3/loss) was associated with lower survival on fluoropyrimidine chemotherapy. LOH in tumour tissue is a significant factor, to be taken into account when TS genotypes are to be considered for outcome prediction.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…Patients with *2/*2 genotype have a good prognosis, but patients with *3/*2 genotype are sometimes included in the good prognosis group 27 and other times in the intermediate or bad prognosis group. 12,26 In a recent work, Uchida et al 29 reported that the loss of heterozygosity at the TS locus in tumor samples of colorectal cancer patients treated with fluoropyrimidine therapy affects tumor response and survival in those patients with a heterozygous TS*2/*3 genotype. In 17 of 22 of these heterozygous cases, a LOH was demonstrated in tumor tissues The authors reported that the response rate of the TS*2/loss tumor genotype patients was 80% and that only 1 of 7 tumors with a genotype of *3/loss showed a response.…”
Section: Correlation Between Ts Genotype and Survivalmentioning
confidence: 99%